Bronchial Artery Chemoembolization With Radiopaque Doxorubicin Eluding Beads in Patients With Malignant Hemoptysis from Metastatic Lung Cancer - Nariman Nezami MD; Christos Georgiades MD, PhD; Kelvin K. Hong MBBCh, MBBS; Ji Buethe MD (Technology in Cancer Research & Treatment, 2022)
Purpose: This pilot study was designed to assess the technical feasibility and safety of bronchial artery chemoembolization with radiopaque doxorubicin eluting beads (DEB-BACE) in patients with malignant hemoptysis from pulmonary metastasis. Materials & Methods: Four patients underwent DEB-BACE using 70-150 μm radiopaque DEB (LC Beads LUMI, Boston Scientific). Beads delivery and deposition were assessed under fluoroscopy and cone beam computed tomography (CT), respectively. Results: All 4 procedures were technically successful. Beads delivery and deposition were successfully visualized under fluoroscopy and cone beam CT guidance in all cases. Hemoptysis was resolved after embolization in all 4 patients. There were no adverse events or immediate or early complications after DEB-BACE. Two patients (50%) required repeat DEB-BACE within 1 week due to recurrent hemoptysis, and 1 patient had DEB-BACE 1.5 years later due to recurrent hemoptysis from the contralateral lung. All targeted lesions decreased in size in follow-up studies (mean 16 months, range 1-33 months). One patient died of progressive cancer disease invading the heart 1 month after DEB-BACE. Conclusions: DEB-BACE using radiopaque LC Beads LUMI loaded with doxorubicin is technically feasible and safe for controlling hemoptysis and cancer progression in patients with metastatic lung tumors. Visualization of beads delivery under fluoroscopy and deposition of beads under cone beam CT facilitate delivery of beads and embolization of bronchial arteries.